Detection of parC gene mutations associated with quinolone resistance in Mycoplasma genitalium: evaluation of a multiplex real-time PCR assay. Issue 3 (19th March 2021) - Bodiyabadu, Kaveesha; Danielewski, Jennifer; Garland, Suzanne M.; Machalek, Dorothy A.; Bradshaw, Catriona S.; Birnie, Joshua; Ebeyan, Samantha; Lundgren, Marie; Murray, Gerald
Abstract : Introduction. Increasing levels of antibiotic resistance are complicating treatment for the sexually transmitted pathogen Mycoplasma genitalium . Resistance to fluoroquinolones is associated with mutations in the parC gene. Although the precise mutations conferring resistance are not fully understood, the single nucleotide polymorphism (SNP) G248T/S83I is most implicated. Aim. To evaluate the performance of the MG+ parC (beta2) assay (SpeeDx, Australia), which detects single nucleotide polymorphisms (SNPs) in the parC gene at amino acid position S83 (A247C/S83R, G248T/S83I, G248A/S83N) and D87 (G259A/D87N, G259T/D87Y, G259C/D87H). Methods. Clinical samples were analysed by MG+ parC (beta2) assay and results compared to Sanger sequencing. Sensitivity, specificity, and predictive value for treatment failure were calculated. Results. From analysis of 205 samples, the MG+ parC (beta2) assay performed with a high sensitivity 98.2% (95% CI:90.3–100) and specificity 99.3% (95% CI:96.3–100) for parC SNP detection with a kappa of 0.97 (95% CI:0.94–1.00). The predictive value of G248T/S83I detection (the most common SNP, prevalence of 13% in the study population) was analysed with respect to treatment failure (patients received sequential doxycycline-moxifloxacin). The positive-predictive-value for moxifloxacin failure after detection of S83I was only 44% (95% CI:24.4–65.1), while negative-predictive-value was high at 96.9% (95% CI:92.7–99.0), suggesting that other SNPs are contributing to resistance. Conclusion. MG+ parC (beta2) performed with high concordance compared to Sanger sequencing. Such qPCR assays can assist in understanding causes of treatment failure, inform the development of diagnostic assays, and can be applied to surveillance of mutations in populations. Due to an incomplete understanding of the basis for fluoroquinolone resistance, such tests do not appear to be ready for clinical application.